Landmark-Based Wing Morphometrics for Three Holotrichia Beetle Species (Coleoptera, Scarabaeoidea) - Pengliang Pan; Shibao Guo; Fangmei Zhang; Zhou Zhou (Biology)
The scarab beetle is an herbivorous pest that causes considerable damage to various agricultural crops. The characteristics of the hind wings have rarely been utilized as indicators for species identification, particularly within the genus Holotrichia. To evaluate the potential of hind wing traits in species identification and gender differentiation, we extracted 25 landmarks from 125 samples of three beetle species (Holotrichia diomphalia, H. titanis, and H. oblita) using TPSDig2 v2.31, with each hind wing image analyzed three times. These landmarks were employed to analyze variations in wing size and shape among species and sexes, and a cross-validation test was conducted in MorphoJ v1.06 to assess classification accuracy. The results demonstrate that both female and male samples exhibit significant differences in wing size and shape variations across species, but not between sexes. Allometry accounts for 16.92% and 25.35% of total shape variation in females and males, separately. After correcting for allometric effects, classification accuracy improves for these beetles. From further analysis, it can be observed that female wings exhibit a wider and shorter morphology in comparison to the more slender and elongated wings of males. In terms of interspecific differences, H. oblita females displayed narrow and elongated wings, whereas H. diomphalia females had a more rectangular wing shape. Among males, the degree of wing narrowness decreased in the order of H. oblita, H. titanis, and H. diomphalia.